Effect of green machining on distortion and surface finishing in advanced ceramic - Bukvic, Gill [UNESP]; Fiocchi, Arthur A. [UNESP]; Sanchez, Luiz E. A. [UNESP]; Fortulan, Carlos A.; Marinescu, Ioan D. (My University, 2012)
An alternative for grinding of sintered ceramic is the machining on the green state of the ceramic, which presents easy cutting without the introduction of harmful defects to its mechanical resistance. However, after sintering there are invariably distortions caused by the heterogeneous distribution of density gradients, which are located in the most outlying portions of the compacted workpiece. In order to minimize these density gradients, this study examined the influence of different allowance values and their corresponding influence in distortion after sintering alumina specimens with 99.8% purity by turning operation using cemented carbide tool. Besides distortion, other output variables were analyzed, such as tool wear, cutting force and surface roughness of green and sintered ceramics. Results showed a distortion reduction up to 81.4%. Green machining is beneficial for reducing surface roughness in both green and sintered states. Cutting tool wear has a direct influence on surface roughness and cutting force.
Keywords: Density gradient; Distortion; Green machining; Surface finishing; Uniaxial pressing